(untitled) (Ha Noi, 2009)
The study provide economic and social arguments on different options for women's retirement age in Vietnam to serve as a basis for further consultation and policy dialogue with the Government.
Keywords: Retired executives,Civil service pensioners,Quy định nghỉ hưu,Dịch vụ trợ cấp người nghỉ hưu